A Forecasting Model for MSMEs of Manufacturing and Engineering Sector of India. Issue 1 (March 2021) - Das, Sourav Kumar; Chakraborty, Mainak
Micro, small and medium enterprises (MSMEs) are the key ingredients for economic growth of any country. The engineering and manufacturing sector has an important role to play in this development. This sector contributes to around 40% of the industrial production. This also supports the Make in India movement that has been initiated by Government of India. This sector employs around 15 million people as per the recent survey by Government of India, making it the second largest source for employment, after agriculture. The engineering and manufacturing sector also witnessed a steady growth. This sector employs more casual labours than the permanent workers. Their concentration also depends on the availability of resources as well as the infrastructure. The growth and development also depend on the economic and political scenarios. This study concentrates on factors like correlation among employers, employees and other economic factors based on a time series analysis of data gathered from registered MSMEs in India. The time series taken here is simple seasonal time series analysis.